Impactos generados por Muchik Feria Internacional de Turismo 2018, en el desarrollo del turismo de reuniones y eventos, en Trujillo - Bazán Rojas, Marcia Stephanie (2022)
This research was carried out with the purpose of knowing about the Impacts generated by Muchik International Tourism Fair 2018, in the development of tourism for meetings and events, in Trujillo, the variables being economic and tourist impacts._x000D_ In order to fulfill the study objectives, the Inductive - Deductive, Analytical - Synthetic methods were applied; techniques such as file review, which allowed us to better analyze the organization of the Fair; the survey, which was conducted to the exhibitors who participated; and interviews with the former president and current president of CADETUR La Libertad, as well as the former Regional Assistant of IPerú. Among the instruments used were: survey questionnaire and interview to measure the economic and tourist impact variables_x000D_ With this research, we have been able to verify that Muchik Fair 2018 has had a great impact, within the Tourism of Meetings and Events, turning it into a tourist strategy for the city of Trujillo; due to the number of negotiations (between 21-30 negotiated negotiations; and 11-21 executed negotiations), an average expense of more than 600 soles; and 113 jobs. However, it had more than 326 tourists, and it has a profile of this convention tourist that has been forged during the event.